2021
DOI: 10.1038/s41598-021-02296-x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of optical coherence tomography angiography metrics in primary angle-closure glaucoma and normal-tension glaucoma

Abstract: To investigate the peripapillary vascular metrics in early normal tension glaucoma (NTG) and early primary angle closure glaucoma (PACG) eyes using optical coherence tomography angiography (OCT-A). One or both eyes of each subject were imaged for a 3 × 3 mm peripapillary region by swept-source OCT-A (DRI-OCT Triton, Topcon, Japan) and assessed by an automated MATLAB program. OCT-A metrics including circumpapillary vessel density (cpVD) and fractal dimension (cpFD) were compared. Their association with visual f… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 40 publications
(40 reference statements)
3
15
0
Order By: Relevance
“…Advances in imaging diagnostic techniques have revealed more anatomical factors associated with primary angle-closure glaucoma, helping to develop a deeper understanding of disease pathology. The optic disc nerve and its vascular structures are important in the pathophysiology of primary angle-closure glaucoma 14,23,30,32 . In our meta-analysis, thinner retinal nerve fiber layer was significantly associated with primary angle-closure glaucoma.…”
Section: Discussionmentioning
confidence: 61%
See 3 more Smart Citations
“…Advances in imaging diagnostic techniques have revealed more anatomical factors associated with primary angle-closure glaucoma, helping to develop a deeper understanding of disease pathology. The optic disc nerve and its vascular structures are important in the pathophysiology of primary angle-closure glaucoma 14,23,30,32 . In our meta-analysis, thinner retinal nerve fiber layer was significantly associated with primary angle-closure glaucoma.…”
Section: Discussionmentioning
confidence: 61%
“…1. Appendix Table A4, available at http://links.lww.com/OPX/A658, shows the characteristics of the remaining 45 related studies 12–56 . Two of the 45 articles were conducted from the same cohort 44,45 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A recent study found that among patients with POAG and PACG, both with elevated IOP, choroidal microvasculature dropout was greater in POAG, indicating a role for primary choroidal ischemic injury in the pathophysiology of POAG. 27 Another study by Shen et al 28 demonstrated that the reduction in circumpapillary vessel density was more pronounced in patients with normal tension glaucoma who had normal IOP than in patients with PACG who had high IOP. A study by Cheng et al 29 also showed that in the subgroup with the lowest IOP in POAG, the choriocapillaris vessel density decreased the fastest.…”
Section: Discussionmentioning
confidence: 99%